Elder-friendly emergency services in Brazil: necessary conditions for care - Mariana Timmers dos Santos; Maria Alice Dias da Silva Lima; Paula Buchs Zucatti (Revista da Escola de Enfermagem da USP)
Abstract OBJECTIVE To identify and analyze the aspects necessary to provide an elder-friendly emergency service (ES) from the perspective of nurses. METHOD This is a descriptive, quantitative study using the Delphi technique in three rounds. Nurses with professional experience in the ES and/or researchers with publications and/or conducting research in the study area were selected. The first round of the Delphi panel had 72 participants, the second 49, and the third 44. An online questionnaire was used based on a review of the scientific literature with questions organized into the central dimensions of elder-friendly hospitals. A five-point Likert scale was used for each question and a 70% consensus level was established. RESULTS There were 38 aspects identified as necessary for elderly care that were organized into central dimensions. CONCLUSIONS The study's results are consistent with the findings in scientific literature and suggest indicators for quality of care and training for an elder-friendly ES.